Benefit from the applications of biotechnology in increasing agricultural productivity in Ethiopia - Zera Aweke; Teddy Dibaba; R. A. Gubegna (Global Journal of Plant and Soil Sciences, 2017)
Ethiopia is an agrarian country that can have enormous benefit from the applications of biotechnology for increasing its agricultural productivity. The country is at initial stages of research and development in agricultural biotechnology with scattered efforts underway in various public institutions. Research efforts and applications in crop production include plant tissue culture, biofertilizers and biopesticides, molecular markers for disease diagnosis and genetic diversity. Livestock related applications include artificial insemination, molecular diagnostics, vaccine production and molecular genetic analysis. Infrastructure and skills in recombinant DNA and other cutting edge technologies such as proteomics and bioinformatics are still limited and need to be strengthened. A number of crop production constraints can be solved by using advanced biotechnology tools/products including genetically modified organisms. Cognizant of this, Ethiopia has recently given a due emphasis for capacity building in agricultural biotechnology extending from promoting research, development and education in various public institutions to setting up of an independent agricultural biotechnology research center. The constraints holding back progress in agricultural biotechnology are numerous ranging from poor technical and regulatory capacity to lack of appreciation of opportunities provided by agro-biotechnology by the public and decision makers.